Correct original spelling of Hydropeza queenslandensis Sinclair (Diptera: Empididae) - Sinclair, Bradley J. (Zootaxa, 2018)
While databasing type specimens of Hydropeza Sinclair in the Australian Museum (Sydney), different spellings of a species name in Sinclair (2016) were identified. I herein resolve this nomenclatural issue.